Carbon‐Based Dots Co‐doped with Nitrogen and Sulfur for High Quantum Yield and Excitation‐Independent Emission1. Issue 30 (11th June 2013) - Dong, Yongqiang; Pang, Hongchang; Yang, Hong Bin; Guo, Chunxian; Shao, Jingwei; Chi, Yuwu; Li, Chang Ming; Yu, Ting
<x xml:space="preserve">Abstract</x> Helpful elements: A facile bottom‐up method using citric acid and L‐cysteine as a precursor has been developed to prepare graphene quantum dots (GQDs) co‐doped with nitrogen and sulfur. A new type and high density of surface state of GQDs arises, leading to high yields (more than 70 %) and excitation‐independent emission. FLQY=fluorescence quantum yield.<boxed-text content-type="graphic" position="anchor" orientation="portrait"> </boxed-text>